Balancing the Friction: How a Constitutional Challenge to Copyright Law Could Realign the Takings Clause of the Fifth Amendment - Sanney, Kenneth J. (Science and Technology Law Review, 2014)
With the shift in the focus of the American economy from an agrarian economy to a manufacturing economy to a technology economy, there has been a corresponding shift in the socioeconomic importance of differing types of property from real property to personal property to digital property. Unfortunately, the legal response to this shift has unwisely tipped the balance of property rights in favor of society and away from the individual. In order to support the otherwise laudable intellectual property goal of advancing the arts and sciences, the federal government has moved incrementally down a path that has resulted in the complete devaluation of large swaths of privately owned property simply because that property is digital. A very significant point on this path has been crossed. In spite of the increasing importance of digital property to the American economy, the United States Supreme Court has interpreted the Takings Clause of the Fifth Amendment to provide substantially less protection for digital property than for real property. These rulings have created a constitutional misalignment of economic realities, public policy, and law. Copyright law provides a focused lens for the examination of the resulting misalignment. Through administrative regulations, statutory provisions, and court rulings, the federal government has vested copyright owners with the legal authority to exercise dominion over others’ property in an unprecedented way. We are now at a point where it is illegal for the consumer to alter or sell even lawfully-obtained property. The Digital Millennium Copyright Act authorizes copyright owners to place digital locks onto both digital content and within tangible property such as cellphones and video game consoles. Correspondingly, as we have seen in the Librarian of Congress’s recent ruling that removed the rights of consumers to jailbreak their cellphones and the Capitol Records, LLC v. ReDigi Inc. civil case that ruled that consumers cannot sell their digital music files, the other branches of government are complicit in this unprecedented shift in property rights. While these actions by the federal government were intended to undergird the public good of advancing the arts and sciences, in reality, they have strengthened the copyright monopoly in an unwarranted manner by eviscerating one of the most important limitations to that monopoly’s power: the first sale doctrine. This Article demonstrates how a Fifth Amendment Takings Clause challenge to narrow provisions of copyright law would present the judiciary with a set of facts that are well suited to allow the judiciary to realign the policy of the Takings Clause with the economic and legal realities of our day. About the Author